One week of l-citrulline supplementation improves performance in trained cyclists - Stanelle, S. T.; McLaughlin, K. L.; Crouse, S. F. (The Journal of Strength and Conditioning Research, 2020)
L-citrulline (CIT) is a nonessential amino acid that is touted as an ergogenic aid for athletic performance because of its purported ability to stimulate nitric oxide production. Although previous research has demonstrated that CIT supplementation over a period of days improves physiological factors such as V[Combining Dot Above]O2 kinetics, no studies to date have explored whether there is a direct benefit to endurance performance. This study used a randomized, double-blind, crossover design to test whether chronic supplementation with pure CIT improves cycling performance over a maltodextrin placebo (PLAC). Nine trained male cyclists (24 ± 3 years; 181 ± 7 cm; 76 ± 13 kg; 4.18 ± 0.51 L·min-1 V[Combining Dot Above]O2max) completed two 7-day supplementation periods (6 g/d of CIT or PLAC) separated by a 7-day washout. Subjects consumed the final 6-g dose 2 hours before the cycling performance evaluation, which consisted of a 40-km time trial (TT) followed by a supramaximal sprint repeat task (SRT). Paired t-tests and repeated-measures analysis of variance (alpha = 0.05) were used to analyze TT and SRT data, respectively. CIT supplementation produced an improvement in TT time of 5.2% that trended toward significance (p = 0.08). Furthermore, CIT promoted a significant increase in average heart rate, average rating of perceived exertion, and average power throughout the TT (p < 0.05). However, supplementation with CIT did not prevent fatigue during the SRT. Overall, this study is the first to demonstrate that CIT supplementation may provide a modest improvement to endurance cycling performance in trained athletes.